2021
DOI: 10.1038/s41564-021-00983-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota-induced IgA antibodies regulate fungal commensalism in the gut and are dysregulated in Crohn’s disease

Abstract: Secretory immunoglobulin A (sIgA) plays an important role in gut barrier protection by shaping the resident microbiota community, restricting the growth of bacterial pathogens, and enhancing host protective immunity via immunological exclusion. Here, we found that a portion of microbiota-driven sIgA response is induced by and directed towards intestinal fungi. Analysis of the human gut mycobiota bound by sIgA revealed a preference for hyphae; a fungal morphotype associated with virulence. C. albica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 88 publications
3
64
0
3
Order By: Relevance
“… 194 Intriguingly, parallel studies investigating adaptive immunity‐dependent mucosal responses in mice against C albicans (mostly IgA with some IgG1) have shown they are preferentially targeted against antigens expressed only on the tissue‐invasive hyphal morphotype of the fungus and not the less virulent circular yeast form. 195 , 196 These hyphae‐expressing C albicans are associated with worse colitis and extraintestinal diseases. In a cohort of 12 patients with Crohn's disease and 9 healthy controls, the targeting of these hyphal‐associated virulence factors by intestinal antibodies was decreased in CD patients, leading to increased hyphal forms of fungi.…”
Section: Igg Class Switching In Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… 194 Intriguingly, parallel studies investigating adaptive immunity‐dependent mucosal responses in mice against C albicans (mostly IgA with some IgG1) have shown they are preferentially targeted against antigens expressed only on the tissue‐invasive hyphal morphotype of the fungus and not the less virulent circular yeast form. 195 , 196 These hyphae‐expressing C albicans are associated with worse colitis and extraintestinal diseases. In a cohort of 12 patients with Crohn's disease and 9 healthy controls, the targeting of these hyphal‐associated virulence factors by intestinal antibodies was decreased in CD patients, leading to increased hyphal forms of fungi.…”
Section: Igg Class Switching In Inflammatory Bowel Diseasementioning
confidence: 99%
“…In a cohort of 12 patients with Crohn's disease and 9 healthy controls, the targeting of these hyphal‐associated virulence factors by intestinal antibodies was decreased in CD patients, leading to increased hyphal forms of fungi. 195 Thus, by selectively targeting for pathogenic forms of the same fungus over commensal forms, the intestinal humoral immune response can promote homeostasis and ward off distinct morphotypes that are pathogenic if they gain access to the systemic system. 197 Similar disparate antibody responses to distinct genetic phase variations of a single bacterium species have also been reported.…”
Section: Igg Class Switching In Inflammatory Bowel Diseasementioning
confidence: 99%
“…B. thetaiotaomicron and L. johnsonii increased IgA secretion in the colon, which was correlated with a decrease in E. coli , E. faecalis and C. glabrata populations in mice [ 79 ]. In line with this observation, the absence of secretory IgA increased C. albicans hyphal growth in the mouse gut, suggesting that IgA is involved in the control of fungal commensalism in the gut [ 36 , 80 , 81 ]. Doron et al showed that IgA produced in the gut plays a role in regulating intestinal fungal commensalism and offers a protective mechanism that might be dysregulated in CD patients [ 80 ].…”
Section: Impact Of Colonic Inflammation On the Gut Microbiota And How...mentioning
confidence: 73%
“…The mycobiota-induced secretory immunoglobulin A (sIgA) preferentially targets fungal hyphae and thereby regulates fungal commensalism in the human intestine. C. albicans colonization in the gut was identified as a potent sIgA inducer and seems to thereby influence its own hyphal morphogenesis to maintain commensalism [28] . Shifts in Candida abundance can be linked to multiple disease types such as inflammatory bowel disease, including Crohn’s disease and ulcerative colitis, alcohol-associated liver disease and alcoholic hepatitis [29] , [30] , [31] , [32] .…”
Section: The Mycobiome and Its Environmentmentioning
confidence: 99%